2018
DOI: 10.1007/s13205-018-1131-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of gluco-amylase production from Aspergillus spp. for its use in saccharification of liquefied corn starch

Abstract: Fungal gluco-amylase is required for the production of sugars from starchy substrates. Commercially available fungal gluco-amylase is quite costly which makes the process uneconomical. This study was undertaken to standardize physico-chemical parameters for optimum production of gluco-amylases from spp. Two fungal cultures, i.e., and , were compared for gluco-amylase activity both under stationary and shake flask conditions. Among two fungal cultures, maximum gluco-amylase activity was shown by (243.09 U/ml) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Starch agar slants were used for the growth of selected amylolytic bacterial isolates and incubated at 37°C for 48 h. For amylase production study, a loopful of culture was inoculated in starch supplemented minimal media (SSMM) broth as suggested by Jain and Katyal [12] and incubated at 37°C. Fungal culture (Aspergillus niger) was grown on PDA medium at 28°C for 4 days.…”
Section: Inoculum Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…Starch agar slants were used for the growth of selected amylolytic bacterial isolates and incubated at 37°C for 48 h. For amylase production study, a loopful of culture was inoculated in starch supplemented minimal media (SSMM) broth as suggested by Jain and Katyal [12] and incubated at 37°C. Fungal culture (Aspergillus niger) was grown on PDA medium at 28°C for 4 days.…”
Section: Inoculum Preparationmentioning
confidence: 99%
“…Earlier studies have also reported that amylase activity declined significantly after 24 h of incubation that can be due to poor availability of nutrients, accumulation of toxic metabolites and fast metabolism. [12,21]…”
Section: Periodic Estimation Of Selected Cultures (Am1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Saccharification refers to the process in which tissues rich in starch or cellulose undergo acidolysis or hydrolysis to produce sweet substances in the presence of water [10]. Saccharification of sweetpotato storage roots is a process in which the starch is converted into soluble sugar during cooking.…”
Section: Introductionmentioning
confidence: 99%